Aporte de Galileo a la ciencia moderna. (2022)
In this paper aristothelic philosophy elements are shown, those ones predetermine modern science. The main point turns around the relationship among Caldeo and Platon and it supports a thesis that is pretended from reading the text of Koyré, which is to think that among the ancient thought and the modern thought (galilean) there is no break, but, on the contrary, continuity. Thesis that some philosophers like Kuhn, for example, reject and even defend the opposite point of view.